2006
DOI: 10.1074/jbc.m603361200
|View full text |Cite
|
Sign up to set email alerts
|

The Potassium Channel KAT1 Is Activated by Plant and Animal 14-3-3 Proteins

Abstract: 14-3-3 proteins modulate the plant inward rectifier K؉ channel KAT1 heterologously expressed in Xenopus oocytes. Injection of recombinant plant 14-3-3 proteins into oocytes shifted the activation curve of KAT1 by ؉11 mV and increased the on . KAT1 was also modulated by 14-3-3 proteins of Xenopus oocytes. Titration of the endogenous 14-3-3 proteins by injection of the peptide Raf 621p resulted in a strong decrease in KAT1 current (ϳ70% at ؊150 mV). The mutation K56E performed on plant protein 14-3-3 in a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 40 publications
0
49
0
2
Order By: Relevance
“…It is well established that animal 14-3-3 proteins activate KAT1 conductance in two ways: by increasing the current density (i.e., the number of active channels in the plasma membrane) and by increasing the channel open probability at a given voltage. As a result of 14-3-3 binding, the channel maximal current increases and the half activation potential, the voltage value at which 50% of the channels are open (V 1/2 ), shifts positive of ;10 mV (Sottocornola et al, 2006(Sottocornola et al, , 2008. All mutants generated voltage-dependent, slowly activating, inward rectifying K + currents, typical of the wild-type KAT1 channel ( Figure 1B).…”
Section: -3-3 Binding To Kat1 Is Regulated By S676 Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that animal 14-3-3 proteins activate KAT1 conductance in two ways: by increasing the current density (i.e., the number of active channels in the plasma membrane) and by increasing the channel open probability at a given voltage. As a result of 14-3-3 binding, the channel maximal current increases and the half activation potential, the voltage value at which 50% of the channels are open (V 1/2 ), shifts positive of ;10 mV (Sottocornola et al, 2006(Sottocornola et al, , 2008. All mutants generated voltage-dependent, slowly activating, inward rectifying K + currents, typical of the wild-type KAT1 channel ( Figure 1B).…”
Section: -3-3 Binding To Kat1 Is Regulated By S676 Phosphorylationmentioning
confidence: 99%
“…Currently it is not known how the activity of the KAT1 channel is integrated in this scenario. Some indirect evidence for a regulatory modulation of KAT1 by the 14-3-3 proteins can be anticipated from data, which show that activity and trafficking of the channel are promoted by an overexpression of 14-3-3 proteins (Sottocornola et al, 2006(Sottocornola et al, , 2008. So far, direct binding of 14-3-3 proteins to the KAT1 channel has not been demonstrated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that posttranslational regulation is an important mechanism for regulation of K + channel activities in plant cells [13,[38][39][40]. One of the examples is the regulation of AKT1 activity by a protein kinase AtCIPK23.…”
Section: A Complex K + Uptake Regulatory Pathway In Arabidopsis In Rementioning
confidence: 99%
“…14-3-3 proteins are a family of evolutionary conserved dimeric proteins that accomplish a wide range of regulatory roles in eukaryotes (Fu et al, 2000). In plants, in addition to the plasma membrane transport through the regulation of the H þ -ATPase activity, 14-3-3s are involved in the control of gene expression, in the cellular trafficking, in the control of the activities of diverse enzymes of metabolism, in the hormone signaling, and in general in the coordination of different signal transduction pathways (Aducci et al, 2002;Sottocornola et al, 2006;Camoni et al, 2011;Schoonheim et al, 2009;Denison et al, 2011). Lots of evidence suggest also a role of 14-3-3s in the plant response to stress conditions (G€ okirmak et al, 2010): environmental and biotic stresses can affect the expression levels of 14-3-3 genes (Chevalier et al, 2009) and also a large number of stresserelated proteins have been identified as 14-3-3 clients (Chang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%